Metacognitive Strategies in Teaching Reading to Primary Students - Tandean, Diana (Widya Mandala Catholic University Surabaya, 2020)
This study is aimed to cater to the needs of professionals in raising young learners’ awareness of their own reading comprehension, educators can implement metacognitive strategy as one of the solutions. Therefore this study aims to know the effectiveness of metacognitive strategy in teaching reading to primary students. The grand theory employed in this study is the six sequential reading strategies proposed by Brown, Palinscar and Armbruster’s (1984). The research method is pre-experimental study with three groups of third graders as the participants. The researcher designed a reading assignment for each treatment, as well as a reading test as the research instrument. The pre-test and post-test data was analyzed using paired t-test. The data shows a significant difference between pre-test and post-test scores among all three groups.